2021
DOI: 10.1017/ipo.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Party–group interactions in Southern Europe: evidence from an expert survey

Abstract: Despite the development of empirical research on the relations between parties and interest groups, the topic is still understudied and presents several shortcomings. On the one hand, this relationship has been studied mostly from the political parties' point of view. On the other, there is a lack of consensus regarding the determinants of party–group connection. This study aims to advance our knowledge on the topic by examining the relationship between interest groups and political parties in Southern Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…All else being equal (i.e., groups' resources and policy characteristics), the greater ideological proximity between business interests and the new executive is the most likely factor to account for the increased degree of preference attainment (and overall satisfaction with the NRRP) shown by this type of interests. Indeed, a recent study (Lisi, 2022, 109) empirically demonstrated how Lega and Forza Italia are ideologically proximate to business associations (i.e., Confindustria and Confcommercio ) and electoral studies recognize that both right-wing parties are generally more voted by self-employed as well as by small and big entrepreneurs (Comodo and Forni, 2018, 215), in so showing a great deal of ideological proximity with business groups in giving representation to interests present in society. Moreover, the ideological proximity argument is reinforced by the role played by the relevant ministries in the definition of the NRRP components and objectives, representing a critical venue for the interaction between interest groups and parties.…”
Section: Discussion Of the Findings And Future Researchmentioning
confidence: 99%
“…All else being equal (i.e., groups' resources and policy characteristics), the greater ideological proximity between business interests and the new executive is the most likely factor to account for the increased degree of preference attainment (and overall satisfaction with the NRRP) shown by this type of interests. Indeed, a recent study (Lisi, 2022, 109) empirically demonstrated how Lega and Forza Italia are ideologically proximate to business associations (i.e., Confindustria and Confcommercio ) and electoral studies recognize that both right-wing parties are generally more voted by self-employed as well as by small and big entrepreneurs (Comodo and Forni, 2018, 215), in so showing a great deal of ideological proximity with business groups in giving representation to interests present in society. Moreover, the ideological proximity argument is reinforced by the role played by the relevant ministries in the definition of the NRRP components and objectives, representing a critical venue for the interaction between interest groups and parties.…”
Section: Discussion Of the Findings And Future Researchmentioning
confidence: 99%